2021
DOI: 10.1007/s00217-021-03827-6
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior and microstructure of Pickering emulsions based on different concentrations of gliadin/sodium caseinate nanoparticles

Abstract: The properties of Pickering emulsion stabilized by different gliadin/sodium caseinate nanoparticle (Gli/CAS NPs) concentrations were investigated through physical stability, rheological properties, and microstructure observation. The results suggested that the higher the particle concentration, the smaller the size of the emulsion. The Pickering emulsion with 4% Gli/ CAS NPs displayed the smallest particle size and higher stability. All the Pickering emulsion samples showed pseudoplastic behavior which is regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…4 C. For all of the samples, G' was always larger than G'', showing frequency dependence, which indicated that the Pickering emulsion might form a high internal phase gel structure. The interconnected network formed between the adsorbed and without adsorbed protein particles in the emulsions also improved the elasticity of the emulsion ( Xu et al, 2021 ). With the increase of BSPI-C3G particle concentration, the elasticity of emulsion gradually increased and then remained at a relatively high level, which may be due to the increase in the number of droplet–droplet interactions, indicating that BSPI-C3G particle-stabilized Pickering emulsion with an interfacial three-dimensional network promoted the formation of the elastic gel-emulsion network ( Liu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 C. For all of the samples, G' was always larger than G'', showing frequency dependence, which indicated that the Pickering emulsion might form a high internal phase gel structure. The interconnected network formed between the adsorbed and without adsorbed protein particles in the emulsions also improved the elasticity of the emulsion ( Xu et al, 2021 ). With the increase of BSPI-C3G particle concentration, the elasticity of emulsion gradually increased and then remained at a relatively high level, which may be due to the increase in the number of droplet–droplet interactions, indicating that BSPI-C3G particle-stabilized Pickering emulsion with an interfacial three-dimensional network promoted the formation of the elastic gel-emulsion network ( Liu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was no stratification in any of the emulsions with different oil phase volume fractions; they were still uniform milky white liquids ( Figure 3 C). As shown in Figure 4 , in the observation of optical microstructure, the increased oil phase volume fraction led to an increase in emulsion droplet size and uneven distribution, which was due to the increase in the oil phase volume fraction, and oil droplets tended to aggregate and form a lipid layer [ 42 ]. The droplet size of the emulsions with 5% and 10% volume fractions of the oil phase did not change significantly after 15 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Protein variants, drawn from diverse sources like mung beans (Mohammadian et al 2021), whey protein, notably sodium caseinate (Peng et al 2020;Xu et al 2021), and proteins derived from soy and wheat (Sun et al 2023a;Kevij et al 2020), are integral components in the process of nanoencapsulation employing the described method. Zein, valued for its versatility and cost-effectiveness, is a frequent choice as a polymer in fabricating PNPs utilizing the pH-driven technique.…”
Section: Ph-drivenmentioning
confidence: 99%